Development of a docetaxel micellar formulation using poly(ethylene glycol)–polylactide–poly(ethylene glycol) (PEG–PLA–PEG) with successful reconstitution for tumor targeted drug delivery - Taehoon Sim; Jae Eun Kim; Ngoc Ha Hoang; Jin Kook Kang; Chaemin Lim; Dong Shik Kim; Eun Seong Lee; Yu Seok Youn; Han-Gon Choi; Hyo-Kyung Han; Kwon-Yeon Weon; Kyung Taek Oh (Drug Delivery, 2018)
Docetaxel (DTX)-loaded polymeric micelles (DTBM) were formulated using the triblock copolymer, poly(ethylene glycol)–polylactide–poly(ethylene glycol) (PEG–PLA–PEG), to comprehensively study their pharmaceutical application as anticancer nanomedicine. DTBM showed a stable formulation of anticancer nanomedicine that could be reconstituted after lyophilization (DTBM-R) in the presence of PEG 2000 and D-mannitol (Man) as surfactant and protectant, respectively. DTBM-R showed a particle size less than 150 nm and greater than 90% of DTX recovery after reconstitution. The robustly formed micelles might minimize systemic toxicity due to their sustained drug release and also maximize antitumor efficacy through increased accumulation and release of DTX from the micelles. From the pharmaceutical development point of view, DTBM-R showing successful reconstitution could be considered as a potent nanomedicine for tumor treatment.